Do Badges Affect Intrinsic Motivation in Introductory Programming Students?. (February 2020) - Facey-Shaw, Lisa; Specht, Marcus; van Rosmalen, Peter; Bartley-Bryan, Jeanette
Background. Programming is a challenging and highly important topic for introducing learners to our digital world. Research has shown that motivation plays a key role in programming performance.Gamification usingdigital badges has the potential to influence motivation, provide social recognition and encourage learner participation. More research is recommended to evaluate its motivational impact in different contexts. Intervention. This research explores the effects of badges on theintrinsic motivation levels ofintroductory programming students within ahigher education institution. The course is offered during the first year of the programme. We report the results of a baseline study without badges and four subsequent badge experiments of different designs over a four-year period. Methods. This quasi-experimental study followed a pre-test/post-test design to measure the effects of badges on theintrinsic motivation levels of university-levelintroductory programming students. Badges were designed and implemented. Feedback via focus groups and a post-badge survey was collected. Results. Findings are inconclusive as the quantitative results suggest that badges did not increaseintrinsic motivation scores. Contrastingly, badge survey and qualitative data indicate that badges were received more positively on average. Discussion. We analyse and discuss the results within the context of motivation and the programming discipline, and discuss external factors that may impact the relationship betweengamification and motivation. Conclusion. Further research is necessary to investigate whethergamification, through the use ofdigital badges, can foster positive intrinsic motivational results, particularly in the well-known challenging domain ofintroductory programming .